Intermediation in a directed search model - Klaus Kultti; Tuomas Takalo; Oskari Vähämaa (Bank of Finland, 2018)
We study the ability of competitive coordination service platforms (such as auction sites and real estate agents) to facilitate trade in a directed search model where buyers have unit demands and each seller only has one good to sell. The sellers' capacity constraint leads to a coordination problem as in a symmetric equilibrium without intermediation some sellers receive multiple buyers while some are left without any customers. We compare this equilibrium to one where sellers and buyers can choose to become intermediaries who coordinate the meetings. We find that roughly 20 percent of agents become intermediaries. As a result, a large part of the supply and demand in the economy vanishes. Moreover, the large amount of intermediaries actually reduces the meeting efficiency. Jointly, these effects imply that the gains from trade are roughly 25 percent lower than in the economy without intermediation.
URN:NBN:fi:bof-201810262106
Keywords: D4; L1; 330